2003
DOI: 10.1046/j.1365-2273.2003.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

The AAO-HNS Committee on Hearing and Equilibrium Guidelines for the diagnosis and evaluation of therapy in Meniere's disease: have they been applied in the published literature of the last decade?

Abstract: To assess how effectively the American Academy of Otolaryngology-Head and Neck Surgery Committee on Hearing and Equilibrium (AAO-HNS CHE) guidelines for the diagnosis and evaluation of therapy in Meniere's disease have been applied in the last 11 years of published literature. This was a MedLine-based review. Some 79.7% of papers attempted to use the AAO-HNS CHE guidelines. However, only 50% of these publications managed to use the AAO-HNS CHE criteria in the diagnosis and evaluation of therapy correctly. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 6 publications
2
36
0
5
Order By: Relevance
“…In addition, patients with mild symptoms may not have been diagnosed, as patients may suffer from variable auditory and/or vestibular symptoms for several years before they meet the diagnostic criteria for MD [da Costa et al, 2002]. Furthermore, Thorp et al [2003] observed that despite the existence of widely accepted diagnostic criteria, the majority of clinicians do not always adhere to them when making a diagnosis of MD. MD remains a difficult disease to diagnose, especially in the early stages when not all its symptoms are present [Sajjadi and Paparella, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with mild symptoms may not have been diagnosed, as patients may suffer from variable auditory and/or vestibular symptoms for several years before they meet the diagnostic criteria for MD [da Costa et al, 2002]. Furthermore, Thorp et al [2003] observed that despite the existence of widely accepted diagnostic criteria, the majority of clinicians do not always adhere to them when making a diagnosis of MD. MD remains a difficult disease to diagnose, especially in the early stages when not all its symptoms are present [Sajjadi and Paparella, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the results of the electorocochleogram and/or VEMP disagreed with clinical symptoms and disease history. The guidelines for M áeni àere's disease from the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) Committee of Hearing and Equilibrium dene M áeni àere's disease mostly in terms of its symptoms, 20,21 describing the probability of the disease as possible, probable, deˆnite, and certain. Certain M áeni àere's disease is deˆned as deˆnite with histopathologic conˆrmation; objective diagnosis with histological conˆrmation is currently virtually impossible.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…An assessment of the application of the AAO-HNS guidelines for MD diagnosis across the published literature from 1989 to 1999 showed that 80% of studies used the guidelines, but that <40% used them correctly [Thorp et al, 2003]. Bauer et al [2015] altered the diagnostic inclusion criteria, including the number and type of encounter, and found a reduction in prevalence of up to 35% when using the most restrictive criteria compared to the broadest.…”
Section: Introductionmentioning
confidence: 99%